Socio-philosophical analysis of the crisis of liberal democracy - M.V. Manannikova; I.G. Balakhontseva; M.V. Lutcev (Интеллект. Инновации. Инвестиции, 2020)
The appeal to the problem of the state of modern liberal democracy is relevant due to the positioning of its model as the most universal, as a result of which it is recognized as the most optimal way of social existence. The empirical analysis of this legal system is at odds with the theoretical views of the supporters of this position, so the purpose of this article is to analyze the problem of the existence and functioning of the model of liberal democracy and determine the possible causes of its crisis. The analysis of the sources used in this article allows us to identify both the strengths of the studied form of the democratic system and its shortcomings, dissimulated by its apologists. The study of democracy as a social phenomenon allows us to recognize it as an effective way of existence of society. However, the current state of Affairs in Western society shows that many theoretical concepts of liberal democracy do not find their full manifestation. In this paper, the authors correlate the theoretical foundations of the democratic system presented in the concepts of its apologists (from D. Locke to F. Fukuyama) and critics ( I. A. Ilyin, E. A. Pozdnyakov), who defended the position of unacceptability of blind copying of the "Western" model for Russia. The analysis of the differences between the "idealized" theory of liberal democracy and its practical implementation in the social life of a particular society gives the researcher the opportunity to rationally-critical understanding of this phenomenon and, as a consequence, a pragmatic attitude to its "mechanistic" implementation on unprepared socio-historical soil. In this work, the authors used methods of analysis, content analysis of text sources of information in combination with a comparative approach. The study revealed that the main system-forming values of liberal democracy, such as personal freedom, inviolability of interests and human rights and their priority over similar interests and rights of society and the state, in modern conditions have undergone a large-scale devaluation. The result of the study was the justification of the position according to which lobbying the concept of "democratization" as a universal model of socio-political existence, without taking into account the specifics of specific societies and States, generates a well-founded skeptical attitude to it. Considering the socio-political structure of Russian society, the authors came to the conclusion that due to its cultural and historical specificity, the rejection of the liberal model of democracy is quite natural.